Detecting changes in quality‐of‐life over time in patients with peripheral vascular malformations: the OVAMA project. (1st June 2020) - Lokhorst, M.M.; Horbach, S.E.R.; Waner, M.; O, T.M.; van der Vleuten, C.J.M.; Mokkink, L.B.; van der Horst, C.M.A.M.; Spuls, P.I.
Summary: Vascular malformations are a group of rare congenital (present at birth) vessel anomalies. Mostly visible as a bumpy mass different in colour from normal skin, they can cause disfigurement of the face or body. Patients often experience pain, physical impairment, bleeding, and psycho‐social problems, leading to an overall poor quality of life. Thus, a main goal of treatment is improving their quality of life. Quality of life is measured with questionnaires, which are filled in by patients. To determine if a patient's quality of life improved or worsened after treatment, it is crucial that the questionnaire can detect changes over time. Never has a quality of life questionnaire been studied if it can detect changes in patients with vascular malformations. Consequently, it is impossible to evaluate if current treatments actually improve these patients' quality of life. This study, from the Netherlands and U.S.A., aimed to find out if two widely used quality of life questionnaires, the 'SF‐36' and 'Skindex‐29', were able to detect changes in patients with vascular malformations. Sixty‐seven patients filled in the two questionnaires at two points in time. One group received treatment in between, and another group did not. When filling in the two questionnaires for the second time, patients were also asked if they experienced changes in aspects of quality of life. To deem the questionnaires as able to detect changes, a certain correlation was expected between the experienced change, and change in the scores of the questionnaires. For both questionnaires, the expected correlation was not found. The authors concluded that other questionnaires must be identified or developed to correctly detect changes in quality of life in patients with vascular malformations. This is a summary of the study: Responsiveness of quality‐of‐life measures in patients with peripheral vascular malformations: the OVAMA project